2014
DOI: 10.1111/pace.12557
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐Analysis of Continuous Oral Anticoagulants Versus Heparin Bridging in Patients Undergoing CIED Surgery: Reappraisal after the BRUISE Study

Abstract: Uninterrupted use of OAC in the perioperative of CIED surgery was associated with a reduced risk of bleeding. This strategy should be considered the preferred one in patients at moderate-to-high risk of thromboembolic events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 29 publications
(40 reference statements)
0
20
0
10
Order By: Relevance
“…This study showed no difference in the incidence of TE events or major bleeding complications between the two groups [23]. Two subsequent metaanalyses have shown findings consistent with those of the BRUISE CONTROL and COMPARE trials, including one that included 3744 patients from 14 studies, and found that, in patients undergoing cardiac device implantation, heparin bridging conferred a significantly higher risk of bleeding than continuation of OAC therapy (hazard ratio 3.1; 95% confidence interval [CI] 2.0-4.8), with no significant reduction in the frequency of TE events [20,22]. Together, and as summarized in Table 3, these findings indicate that there are an increasing number of minor procedure/surgery types that can be safely performed without interruption of VKA therapy.…”
Section: Overall Periprocedural Antithrombotic Strategymentioning
confidence: 85%
See 1 more Smart Citation
“…This study showed no difference in the incidence of TE events or major bleeding complications between the two groups [23]. Two subsequent metaanalyses have shown findings consistent with those of the BRUISE CONTROL and COMPARE trials, including one that included 3744 patients from 14 studies, and found that, in patients undergoing cardiac device implantation, heparin bridging conferred a significantly higher risk of bleeding than continuation of OAC therapy (hazard ratio 3.1; 95% confidence interval [CI] 2.0-4.8), with no significant reduction in the frequency of TE events [20,22]. Together, and as summarized in Table 3, these findings indicate that there are an increasing number of minor procedure/surgery types that can be safely performed without interruption of VKA therapy.…”
Section: Overall Periprocedural Antithrombotic Strategymentioning
confidence: 85%
“…There are low-quality to moderate-quality data showing that therapy with VKAs, including warfarin, acenocoumarol, and phenprocoumon, does not require interruption for minor procedures, as shown in Table 2. These include dental procedures (tooth extraction; root canal), skin procedures (biopsy; skin cancer removal), and cataract surgery [20][21][22][23][24][25][26][27]. The 2012 ACCP Antithrombotic Therapy Guidelines give only weak Grade 2C recommendations for continuing VKA therapy in these specific situations involving minor procedures, as they have been associated with a low risk of bleeding [3].…”
Section: Overall Periprocedural Antithrombotic Strategymentioning
confidence: 99%
“…Maintenance of OAC, when compared to heparin bridge with unfractionated heparin or enoxaparin, had a lower risk of perioperative bleeding (OR = 0.25, 95% CI 0.17-0.36, P < 0.00001) (Figure 1). The risk of ATE was very low in our study, with only three events occurring in the group that received uninterrupted warfarin and one event in the group that received heparin bridging (OR = 1.86; 95% CI, 0.29-12.17; P = 0.57) [6].…”
mentioning
confidence: 94%
“…Importantly, device pocket hematomas can necessitate prolonged cessation of anticoagulation with the attendant risk of ATE [6,7]; they can significantly increase the duration and cost of hospitalization; and sometimes reoperation is required. Uslan et al [8] have also highlighted the strong link between pocket hematoma and reintervention, the latter is an independent predictor of ICD infections.…”
mentioning
confidence: 99%
“…Though, it has been believed for many years that temporary withholding the oral anticoagulant (especially warfarin) and bridging with unfractionated or low molecular heparin can be used as a strategy for surgical procedures including device implantation; multiple studies in last few years have indicated that the bridging strategy is associated with the worst clinical outcome and high incidence of hematoma formation [4], [7], [8]. Recent recommendations including the 2016 ESC guidelines on atrial fibrillation [9] suggest that most procedures including device implantations should be performed on therapeutic anticoagulation to achieve the best balance in reducing stroke risk and avoiding hematoma formation.…”
mentioning
confidence: 99%